Réponses

2013-01-03T21:48:44+01:00

pour la 1ére

 

1+2 = 4-1

= 3= 3 donc vrai

 

la 2ème

1+2+4 = 8-1

7 = 7 donc vrai

 

la 3ème

1+2+4+8 = 16-1

15 = 15 donc vrai

2013-01-03T21:56:28+01:00

 2^(0)+2^(1)=2^(2)-1 

 

 2^(0)+2^(1) = 1 + 2 = 3

2^(2)-1 = 4 -1 = 3

Donc 2^(0)+2^(1)=2^(2)-1 

 

2^(0)+2^(1)+2^(2)=2^(3)-1

 

2^(0)+2^(1)+2^(2) = 3 +4 = 7

2^(3)-1 = 8 -1 = 7

Donc 2^(0)+2^(1)+2^(2)=2^(3)-1

 

2^(0)+2^(1)+2^(2)+2^(3)=2^(4)-1

2^(0)+2^(1)+2^(2)+2^(3) = 7 + 8 = 15

2^(4)-1 = 16 -1 = 15

Donc 2^(0)+2^(1)+2^(2)+2^(3)=2^(4)-1